Efficacy and safety of canagliflozin over 52 weeks in patients with type 2 diabetes mellitus and chronic kidney disease. Issue 10 (22nd July 2014) - Yale, J.‐F.; Bakris, G.; Cariou, B.; Nieto, J.; David‐Neto, E.; Yue, D.; Wajs, E.; Figueroa, K.; Jiang, J.; Law, G.; Usiskin, K.; Meininger, G.; et al.
Abstract Aim This study evaluated the efficacy and safety of canagliflozin, a sodium glucose co‐transporter 2 inhibitor, in patients with type 2 diabetes mellitus (T2DM) and within a subset of Stage 3 chronic kidney disease (CKD; estimated glomerular filtration rate [eGFR] ≥30 and <50 ml/min/1.73 m2). Methods In this 52‐week, randomized, double‐blind, placebo‐controlled study, patients (N = 269; mean eGFR, 39.4 ml/min/1.73 m2) received canagliflozin 100 or 300 mg and placebo once daily. Efficacy endpoints included changes in glycated haemoglobin (HbA1c), fasting plasma glucose (FPG), body weight and systolic blood pressure (BP); adverse events (AEs) were also recorded. Results At week 52, canagliflozin 100 and 300 mg reduced HbA1c compared with placebo (−0.19, −0.33 and 0.07%, respectively); placebo‐subtracted differences (95% confidence interval) were −0.27% (−0.53, 0.001) and −0.41% (−0.68, −0.14). Canagliflozin also lowered FPG, body weight and BP versus placebo. Overall AE incidence was 85.6, 80.9, and 86.7% with canagliflozin 100 and 300 mg and placebo, respectively. Osmotic diuresis–related AEs were more common with both canagliflozin doses, and incidences of urinary tract infections and volume depletion–related AEs were higher with canagliflozin 300 mg versus placebo. Decreases in eGFR (−2.1, −4.0 and −1.6 ml/min/1.73 m2) were seen with canagliflozin 100 and 300 mg compared with placebo. Canagliflozin 100 and 300 mg provided median percent reductions in urine albumin to creatinine ratio versus placebo (−16.4, −28.0 and 19.7%). Conclusions Canagliflozin improved glycaemic control and was generally well tolerated in patients with T2DM and within a subset of Stage 3 CKD over 52 weeks.